Effect and toxicity of PF chemotherapy combined with radiotherapy in the treatment of advanced cervical cancer: Medical thermography test - Caixia Gou; Wang Qi; Pengbing Han; Chunlin Zhang (SLAS Technology)
Cancer is one of the leading causes of death worldwide, and treatment options and prognosis for patients with advanced cancer are particularly challenging. PF chemotherapy regimen (the combination of cisplatin and 5-fluorouracil) has been widely used in the treatment of a variety of cancers, and radiotherapy as a local treatment can effectively control tumor growth. This is a prospective clinical trial in which patients were treated with PF chemotherapy combined with radiotherapy. Medical thermal imaging was performed on all patients before, during and after treatment. The examination process involves recording the patient's body surface temperature using a highly sensitive infrared camera and analyzing temperature changes in the tumor area and surrounding tissue. Clinical data on patients were also collected, including treatment response, quality of life scores, and reports of toxic and side effects. Preliminary results showed that PF chemotherapy combined with radiotherapy showed a positive effect in controlling tumor growth, and most patients experienced a reduction in tumor volume. Medical thermal image examination revealed significant changes in tumor area temperature during treatment, which correlated with tumor reactivity. In some cases, thermal imagery shows potential skin and mucosal damage in advance, suggesting the need for early intervention. Thermal imagery also helped assess the impact of treatment on patients' quality of life, such as pain and discomfort by looking at changes in the patient's body surface temperature distribution.